States of passion law, identity, and the social construction of desire - Zylan, Yvonne (New York ; Oxford : Oxford University Press, 2011)
Exploring the role of legal discourse in shaping sexual experience, sexual expression, and sexual identity this book focuses on three topics: anti-gay hate crime laws, same-sex sexual harassment, and same-sex marriage.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Sex and law -- United States; Sociological jurisprudence; Homosexuality -- Law and legislation -- United States